Convincing the Public to Kill: Asian Carp and the Proximization of Invasive Species Threat. Issue 6 (18th August 2019) - Mando, Justin; Stack, Garrett
ABSTRACT: This essay examines the mediation of the threat of Asian carp as an invasive species in American waterways based on analysis of 43 articles published in local and national periodicals from 2009 to 2017. Rhetorical and proximization analysis reveals the consistent establishment of carp as an outsider threat and a continual narrowing of the gap between this threat and the deictic center: the Great Lakes. In addition, the notion of the spectacle of the Asian carp's physiological and behavioral features (i.e. leaping) was found to fade across time in favor of arguments based upon widespread ecosystem and economic damage. This essay argues that the use of these yoked strategies not only prioritizes the threat of Asian carp over other more insidious invasive species but also displays a potentially harmful anti-immigrant preference through metaphor.